SAT0556 Utility and Pitfalls of The FRAX® Tool Results in Brazilian Elderly Population. (15th July 2016) - Malheiro, O.B.; Maia, M.A.M.; Machado, C.J.; de Moraes, E.N.; Kakehasi, A.M.
Abstract : Background: The Fracture Risk Assessment Tool (FRAX®) was introduced by the World Health Organization (WHO) to estimate the 10-year probability of osteoporotic fractures in untreated patients with osteopenia 1 . This tool is validated for Brazilian population since 2013 but the applicability in this developing country has not been confirmed. Objectives: To compare the indication for pharmacological treatment in a Brazilian elderly population considering the results of FRAX® with bone mineral density (FRAX®/BMD), FRAX® without BMD (FRAX®) and of BMD classification according to the WHO. Methods: The study population consisted of patients over 60 years of age from primary care units who had clinical indication for BMD assessment. BMD was undertaken at lumbar spine and femur by dual-energy X-ray absorptiometry (DXA) Hologic Discovery W system (Madison USA, software version 3.3.01) and BMD results were classified according to the WHO criteria. Clinical data was obtained from patient records (secondary osteoporosis, smoking, alcohol consumption, use of glucocorticoids, rheumatoid arthritis, family history (father or mother) with hip fracture, and previous history of fracture) and the 10-year probability of hip and major fractures was calculated using FRAX® tool. Receiving operator curve (ROC) analysis, model calibration and decision curve analysis were used to compare fracture prediction in FRAX® and FRAX®/BMD groups. Results: 1, 000 subjects were included, mean age 76.4 years, 755 (75.5%) women. Osteoporosis, osteopenia and normal BMD were found in 439 (43.9%), 426 (42.6%) e 135 (13.5%) patients, respectively. One hundred and nine (10.9%) patients have already suffered a fragility fracture and 40 of those individuals presented with normal BMD or osteopenia. In 366 (36.6%) patients it was not possible to calculate FRAX® score due to inability of recollection. The application of FRAX® tool would lead to the indication of treatment for 40% of the osteopenic patients and for 62.4% of the osteoporotic patients. Correlations between FRAX and FRAX/BMD were positive and statistically significant for both the 10-year probability of hip fracture and major fracture (0.704 and 0.594, respectively, p<0.001). ROC curve analysis showed that the FRAX/BMD was superior in identifying patients at risk of hip (Figure 1 ) and major fractures. Conclusions: Despite the easy access and simplicity of FRAX® it is not possible to disregard the DXA, especially for patients with risk factor for fragility fractures. References: WHO Scientific group on the assessment of osteoporosis at primary health care level, 2004. www.who.int/chp/topics/Osteoporosis.pdf Disclosure of Interest: None declared